2016
DOI: 10.1186/s12889-016-3531-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation coverage and its determinants among children aged 12-23 months in Atakumosa-west district, Osun State Nigeria: a cross-sectional study

Abstract: BackgroundRoutine immunisation (RI) contributes immensely to reduction in mortality from vaccine preventable diseases (VPD) among children. The Nigerian Demographic and Health Survey, 2008 revealed that only 58 % of children in Osun State had received all recommended vaccines, which is far below World Health Organization (WHO) target of 80 %. We therefore, assessed RI uptake and its determinants among children in Atakumosa-west district of Osun State.MethodsAtakumosa-west district has an estimated population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
68
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 14 publications
(21 reference statements)
19
68
2
Order By: Relevance
“…On the other hand, incomplete-or-noimmunization puts the children at risk of infection from the diseases like Polio, Measles, Tuberculosis and other vaccine preventable diseases (VPDs). And, immunization against the VPDs among the children reduce the risk of mortality and morbidity associated with these deadly infectious diseases 2 . It was estimated that during 2008, seventeen percent of all the deaths among children age 0-59 months were vaccine preventable 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, incomplete-or-noimmunization puts the children at risk of infection from the diseases like Polio, Measles, Tuberculosis and other vaccine preventable diseases (VPDs). And, immunization against the VPDs among the children reduce the risk of mortality and morbidity associated with these deadly infectious diseases 2 . It was estimated that during 2008, seventeen percent of all the deaths among children age 0-59 months were vaccine preventable 3 .…”
mentioning
confidence: 99%
“…This suggests that one in every three children does not achieve their full developmental potential 3 . As part of the public health challenge, India could not achieve the targeted Millennium Development Goals (MDGs) and lagged behind in terms of the child health indicators like nutritional status and immunization 2 . Maintaining an improved child health, thus, becomes a key challenge for social and capital growth in the country 3,4 and through the sustainable development goals India is aiming to achieve zero hunger and malnutrition by 2030.…”
mentioning
confidence: 99%
“…for obstetric factors, place of delivery was reported in three studies [40,53,63], three studies also reported postnatal care follow-up [20,59,63]. Two studies revealed antenatal care follow-up [16,19], likewise maternal tetanus toxoid was reported in two studies [31,47].…”
Section: Modi Able Factorsmentioning
confidence: 98%
“…Greater than 90% and 95% of RBD and PDBD were UVRP and susceptible to HBV infection. Irrespective of blood donor category, the number of VRP was low probably due to the fact that most research participants resided in rural settings [29] . The results of analyses showed that higher HBsAb + seroprevalence was observed among the unvaccinated group (4.68%) compared to the vaccinated group (2.55%).…”
Section: Discussionmentioning
confidence: 99%